Developmental toxicity of zinc oxide nanoparticles on the early life stage of Java medaka (Oryzias javanicus Bleeker, 1856) - Amin, Naweedullah; Vedi, Farida; Navid Wais, Mohammad; Zulkifli, Syaizwan Zahmir; Azmai, Mohammad Noor Amal; Ismail, Ahmad (Universiti Putra Malaysia, 2024)
With a high likelihood of being discharged into aquatic habitats, zinc oxide nanoparticles have been widely employed in a variety of industrial and commercial goods. Concerns over their effects on the environment and human health have grown. This study evaluated the developmental toxicity of zinc oxide nanoparticles (ZnO NPs) on the embryo Java medaka (Oryzias javanicus). With three replicates for each treatment group, the Java medaka embryos were subject to various concentrations of ZnO NPs (10, 25, 50, 100, and 150 μg/L). The heartbeat of treated embryos was increased compared to the control group at 5-, 8-, and 11-days post-exposure (dpe). However, the hatching and mortality of embryos decreased when the concentrations of ZnO NPs increased. Meanwhile, deformities such as low pigmentation, edema (yolk sac and pericardial edema), and spinal deformities were observed in the embryo and larva during the exposure time. Compared to previous studies, ZnO NPs show severe toxicity to selected endpoints at lower concentrations in the embryos of Java medaka.